Osmotic Adjustment and Solutes Accumulation in Leaves of Wheat (Triticum aestivum L.) during Water Deficit - Song Ai Nio; Timothy D. Colmer; Len J. Wade; Gregory Cawthray (Institut Teknologi Bandung, 2011)
This study examined osmotic adjustment (OA) expression and solutes accumulated in leaf segments of wheat cultivar Hartog (with high OA capacity) exposed to polyethylene glycol (PEG). Osmotic adjustment (OA) is one of the traits that contribute to plant tolerance of water deficits. The objectives were to evaluate OA expression as response to increasing PEG concentration and treatment periods, and to examine the concentrations of inorganic and organic solutes in the tissues, as related to OA development at different duration of PEG treatments. The experiment consisted of 4 PEG treatments (0, -0.5, -1.0 and -1.5 MPa), 5 sampling times (0, 12, 24, 48 and 72 h) and 3 replicates. PEG treatments were imposed as -0.5 MPa steps, every 12 h. The leaf segments were sampled for leaf water content, osmotic potential, OA, inorganic solutes (K+, Na+ and Cl-), and organic solutes (glycinebetaine, proline and total soluble sugars). OA was expressed in leaf segments exposed to water deficit under PEG -0.5 MPa, but not at -1.0 MPa or higher. The differences of measurements in PEG -0.5 MPa compared to PEG -1.0 and -1.5 MPa, were clearly observed at 48 h. Amongst the solutes, Na+ and proline contributed to leaf OA.